Knowledge, attitude and practice on dengue fever among international postgraduate students in a public university in Malaysia - Abbasali, Zahra (2020)
Dengue is a vector-borne disease and significant health concern in Malaysia. However, to the international students currently residing in Malaysia, dengue may not be as common or in the list of priority health threat back in their countries which may indirectly increases their risk of dengue. This study aimed at determining the lifetime prevalence rate of dengue fever among international postgraduate students in Universiti Putra Malaysia (UPM) and assessing their current level of knowledge, attitude, and practice in relation to prevention of dengue fever. A cross sectional study was conducted using universal sampling method via an adapted self-administered questionnaire for data collection. Data was analyzed with significant level set at p<0.05. The normality test was checked by using Kolmogorov-Simonov test. Chi-square test, Spearman correlation test, and logistic regression model were applied to test the research hypothesis. A total of 312 respondents were participated with the response rate of 91.7%. The the lifetime prevalence of dengue fever incidence among students was low where respondents had poor level of knowledge and practices but positive attitude on dengue fever. There is a significant (p<0.001) correlation between knowledge and attitude, attitude and practices as well as knowledge and practices respectively. Written material was the significant source of information on dengue fever for the respondents’ level of knowledge. Being female, living in Malaysia more than five years and written material were the significant predictors to good level of knowledge. The significant predictors to positive attitude were age between 31-40 years old while significant predictors to good practices on dengue fever were female and knowledge level on dengue fever. In conclusion, knowledge-based health education and the development of a positive attitude should be further reinforced taking into consideration the gender, age and knowledge delivery mechanism with the aim of improving prevention practices on dengue fever.